2020
DOI: 10.20524/aog.2020.0559
|View full text |Cite
|
Sign up to set email alerts
|

Acute biliary pancreatitis has better outcomes but increased resource utilization compared to acute alcohol-induced pancreatitis: insights from a nationwide study

Abstract: Background The differences in outcomes between acute biliary pancreatitis (ABP) and acute alcohol-induced pancreatitis (AAP) have not been well studied. We sought to examine the differences between ABP and AAP as regards to in-hospital outcomes and resource utilization, using a large nationwide database. Methods We queried the National Inpatient Sample databases 2016 and 2017 using the International Classification of Diseases, 10th revision, Clinical Modification (ICD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Although we documented a lower cost of hospitalization in our population than other studies have reported [37][38][39], all other studies have been conducted in countries with far greater GDP per capita. However, we obtained a similar relation between AAP and costs as two studies [37,38], indicating that AAP is cheaper to treat than biliary AP. Although we did not directly compare AAP with biliary AP, most likely the majority of cases from OAP group were biliary.…”
Section: Discussioncontrasting
confidence: 83%
“…Although we documented a lower cost of hospitalization in our population than other studies have reported [37][38][39], all other studies have been conducted in countries with far greater GDP per capita. However, we obtained a similar relation between AAP and costs as two studies [37,38], indicating that AAP is cheaper to treat than biliary AP. Although we did not directly compare AAP with biliary AP, most likely the majority of cases from OAP group were biliary.…”
Section: Discussioncontrasting
confidence: 83%